The Effect of Harvest Age On The Physical and Chemical Properties of White Oyster Mushrooms (Pleurotus ostreatus) - Tafzi, Fitri; Hasnah , Nur; Nurfaijah, Nurfaijah; Rahmayani, Irma; Nurfitryah, Ayi (Department of Technology of Agricultural product (THP) Jambi University, 2021)
Oyster mushrooms have a delicious taste and contain nutrients. One of the popular oyster mushrooms in the community is white oyster mushrooms (Pleurotus ostreatus). The content and characteristics of oyster mushrooms are influenced by the age of harvest. This study aims to determine the effect of oyster mushrooms harvesting age on physical and chemical properties. This study used a completely randomized design. The treatment is the age of harvesting namely 2, 3, 4, and 5 days after budding. Each experimental unit was repeated 3 times. This research consisted of nursery, incubation, maintenance, and harvesting oyster mushroom. The results showed that harvest age has a significant effect on the height, diameter of the hood and the wet weight but has no effect on the number of stalks and water content of white oyster mushrooms